Who said only military officers can deal with uncertainty? On the importance of uncertainty in edtech data visualisations. - Macgilchrist, Felicitas; Jarke, Juliane (Discourse: Studies in the Cultural Politics of Education, 2025)
AI-powered predictive systems have high margins of error. However, data visualisations of algorithmic systems in education and other social fields tend to visualise certainty, thus invisibilising the underlying approximations and uncertainties of the algorithmic systems and the social settings in which these systems operate. This paper draws on a critical speculative approach to first analyse data visualisations from predictive analytics platforms for education. It demonstrates that visualisations of uncertainty in education are rare. Second, the paper explores uncertainty visualisations in other fields (defence, climate change and healthcare). The paper concludes by reflecting on the role of data visualisations and un/certainty in shaping educational futures. It also identifies practical implications for the design of data visualisations in education.